Effect of CPAP on insulin resistance and HbA1c in men with obstructive sleep apnoea and type 2 diabetes. - West, S; Nicoll, D; Wallace, T; Matthews, DR; Stradling, JR (2007)
BACKGROUND: The effects of continuous positive airway pressure (CPAP) for obstructive sleep apnoea (OSA) on insulin resistance are not clear. Trials have found conflicting results and no appropriate control groups have been used. METHODS: Forty-two men with known type 2 diabetes and newly diagnosed OSA (>10 dips/h in oxygen saturation of >4%) were randomised to receive therapeutic (n = 20) or placebo CPAP (n = 22) for 3 months. Baseline tests were performed and repeated after 3 months. The study was double blind. RESULTS: Results are expressed as mean (SD). CPAP improved the Epworth sleepiness score significantly more in the therapeutic group than in the placebo group (-6.6 (4.5) vs -2.6 (4.9), p = 0.01). The maintenance of wakefulness test improved significantly in the therapeutic group but not in the placebo group (+10.6 (13.9) vs -4.7 (11.8) min, p = 0.001). Glycaemic control and insulin resistance did not significantly change in either the therapeutic or placebo groups: HbA1c (-0.02 (1.5) vs +0.1 (0.7), p = 0.7, 95% CI -0.6% to +0.9%), euglycaemic clamp (M/I: +1.7 (14.1) vs -5.7 (14.8), p = 0.2, 95% CI -1.8 to +0.3 l/kg/min(1000)), HOMA-%S (-1.5 (2.3) vs -1.1 (1.8), p = 0.2, 95% CI -0.3% to +0.08%) and adiponectin (-1.1 (1.2) vs -1.1 (1.3), p = 0.2, 95% CI -0.7 to +0.6 microg/ml). Body mass index, bioimpedance and anthropometric measurements were unchanged. Hours of CPAP use per night were 3.6 (2.8) in the treatment group and 3.3 (3.0) in the placebo group (p = 0.8). There was no correlation between CPAP use and the measures of glycaemic control or insulin resistance. CONCLUSION: Therapeutic CPAP does not significantly improve measures of glycaemic control or insulin resistance in men with type 2 diabetes and OSA.